Exhaled breath condensate efficacy to identify mutations in patients with lung cancer: A pilot study. (3rd April 2022) - Kazeminasab, Somayeh; Ghanbari, Reza; Emamalizadeh, Babak; Jouyban-Gharamaleki, Vahid; Taghizadieh, Ali; Jouyban, Abolghasem; Khoubnasabjafari, Maryam
Abstract: Exhaled breath condensate (EBC) is used to investigate the efficacy of EBC to detect the genetic mutations in patients with lung cancer. Samples of 5 patients and 5 healthy volunteers were collected. DNA was extracted and used for amplification of hotspot regions of TP53 and KRAS genes by using PCR. We performed the mutation analysis by direct sequencing in all subjects. Detected mutations in EBC samples were compared with those of corresponding tumor tissues and there was complete agreement within the detected mutations in EBC and tumorous tissue. EBC can be used as an efficient and noninvasive source for the assessment of gene mutations in patients with lung cancer.